UNLEARNING VIOLENCE, LEARNING HUMANITY: PROMOTING CULTURE OF PEACE THROUGH HUMAN RIGHTS EDUCATION - Muh Asy'ari; Muhammad Fahmi Basyhah Fauzi; Susalti Nur Arsyad (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
Human rights education (HRE) has found its importance in social research today. The rhetoric of how it will bring positive transformations, mainly when associated with a culture of peace, is among many reasons scholars develop all kinds of approaches and ideas to encourage further the practice of HRE in educational institutions, especially universities. Indonesia, with its diverse ethnic and cultural background, is often mentioned to have frequent horizontal conflicts and thus would benefit from HRE in universities. This paper describes the practice of HRE at Universitas Bosowa, one of the universities in Indonesia that has been actively conducting HRE. Library research is used to formulate an elaborate description of the research topic. This paper concluded that the practice of HRE in Universitas Bosowa, with its wide range of learning methods, could be assumed to reach wider audiences outside the academic setting, familiarize students with everyday human rights issues, and manage to promote better human rights regulation in the university.